Analysis of Numeracy Literacy Ability in Fifth Grade Students of SD Negeri Pinayungan V - Ayu Fitri; Tatang Herman (International Conference on Elementary Education, 2023)
Numeracy literacy skills base on must be possessed by fifth grade elementary school students to face the National Assessment (ANBK), this numeracy literacy ability is very necessary not only related to formulas, but also requires students' reasoning power and critical thinking patterns in answering problems that will be needed in aspects of their lives. at home, at school and in the community. This study aims to analyze the numeracy literacy skills of fifth graders at Pinayungan V Elementary School. The subject studied 32 fifth grade students of Pinanyungan V Elementary School, Telukjambe District, Karawang Regency. The research method used in this research is descriptive qualitative. Data collection techniques used in this study using tests, interviews, and documentation. Based on research obtained from 32 students who have low literacy skills as many as 14 students and 18 students who have moderate literacy abilities. The conclusion of this study is that the numeracy literacy ability of fifth graders at SD Negeri Pinayungan V is in the medium category.